Information Constraints and Technology Efficiency: Field Experiments Benchmarking Firms Website Performance - Anwar Adem; Richard Kneller; Cher Li (Center for Economic Studies and ifo Institute (CESifo), 2023)
This study examines the influence of information constraints on firms' efficiency in using digital technologies, focusing on business websites. Through two natural field experiments in the UK, we provide firms with benchmarked performance information on their websites. The experimental designs enable us to assess the salience of the information provided and heterogeneity linked to prior experience and catch-up potential. Our results indicate that performance gaps are not primarily driven by information constraints, as the treatment demonstrates a limited overall impact on motivating firms to improve, with a short-lived effect during the Covid-19 lockdowns. We further support these conclusions using data on website-building software and the number of page views.
Keywords: O32; L25; C93; O33; 330; field experiment; digital technologies; information constraints; performance management; efficiency